Dispersion of regional wall motion abnormality in patients with long QT syndrome. Issue 3 (1st September 1998) - Nakayama, K; Yamanari, H; Otsuka, F; Fukushima, K; Saito, H; Fujimoto, Y; Emori, T; Matsubara, H; Uchida, S; Ohe, T
Abstract : Objective: To examine the left ventricular regional wall motion abnormality and to evaluate dispersion of this abnormality in patients with long QT syndrome. Design: Left ventricular short axis images at basal and middle levels were recorded on videotape and digitised to reconstruct digitised M mode echocardiograms, from which left ventricular wall thickness curves were obtained. The wall thickening time (ThT) was defined as the period in which the instantaneous wall thickness exceeded 90% of the maximum wall thickness. ThT was measured at three segments in each of the septal and free wall sides of the left ventricle, a total of 12 segments. To examine the mechanical dispersion of the left ventricle, the difference between the maximum and minimum ThT of 12 segments in each subject was obtained. Patients: Eight patients with congenital long QT syndrome (averaged QTc interval (SD) 509 (27) ms 1/2 ) and 10 control subjects (QTc interval 397 (26) ms 1/2 ) were examined. Results: The averaged ThT values of the 12 segments pooled from all subjects were correlated with the QT intervals ( r = 0.72, p < 0.005). Thus the averaged ThT in the long QT syndrome patients was longer than in the control subjects (p < 0.005). The segmental variation of ThT in the patients was greater than in the control subjects (p < 0.001). The dispersion of ThT in the patients was therefore larger than in control subjects (p < 0.005). However, the pattern of ThT variation in the patients varied according to the individual subject. Conclusions: There is not only electrical but also mechanical dispersion in the left ventricle of long QT syndrome patients. Regional assessment of ventricular wall motion may allow quantification of the spatial variation of wall motion abnormality.